IMPLEMENTASI FILSAFAT PERENIAL DALAM PENGEMBANGAN PENDIDIKAN MULTIKULTURAL - I Wayan Rudiarta; Putu Wisnu Saputra; Ni Made Ayu Dwi Oktaviani (Padma Sari: Jurnal Ilmu Pendidikan, 2023)
This paper aims to describe the correlation between the implementation of the perennial education philosophy and multicultural education in fostering an attitude of religious moderation. Reflecting on the reality that the concept of religious moderation is a very hot topic to be discussed at the moment, it is deemed necessary to revitalize the concept of multicultural education, which is actually not a new concept. In this revitalization effort, it seems that the perennial educational philosophy as a philosophical basis will contribute to the formation of a curriculum towards multicultural education. In article, the literature review method is used with data analysis techniques in the form of data reduction, verification and conclusion. The results of the study outlined in this paper show that multicultural education is an important substance to be applied in the world of education to foster an open attitude for the development of students cognition. In order to implement multicultural education in the education system, it is necessary to have a curriculum which is the main framework. The preparation of this curriculum is carried out in two processes, namely the formation of a drafting committee and the curriculum preparation process by referring to the principles of relevance, effectiveness, efficiency, continuity and flexibility. It is at this stage that the insertion of perennial philosophy can be carried out and can become a spirit for the structured curriculum. If multicultural education can be implemented, then the government's efforts to create a moderate society, especially in the realm of religion, can be carried out more optimally.